Structural and functional divergence of growth hormone-releasing hormone receptors in early sarcopterygians: lungfish and Xenopus. - Janice K V Tam; Billy K C Chow; Leo T O Lee (PLoS ONE, 2013)
The evolutionary trajectories of growth hormone-releasing hormone (GHRH) receptor remain enigmatic since the discovery of physiologically functional GHRH-GHRH receptor (GHRHR) in non-mammalian vertebrates in 2007. Interestingly, subsequent studies have described the identification of a GHRHR(2) in chicken in addition to the GHRHR and the closely related paralogous receptor, PACAP-related peptide (PRP) receptor (PRPR). In this article, we provide information, for the first time, on the GHRHR in sarcopterygian fish and amphibians by the cloning and characterization of GHRHRs from lungfish (P. dolloi) and X. laevis. Sequence alignment and phylogenetic analyses demonstrated structural resemblance of lungfish GHRHR to their mammalian orthologs, while the X. laevis GHRHR showed the highest homology to GHRHR(2) in zebrafish and chicken. Functionally, lungfish GHRHR displayed high affinity towards GHRH in triggering intracellular cAMP and calcium accumulation, while X. laevis GHRHR(2) was able to react with both endogenous GHRH and PRP. Tissue distribution analyses showed that both lungfish GHRHR and X. laevis GHRHR(2) had the highest expression in brain, and interestingly, X. laevis(GHRHR2) also had high abundance in the reproductive organs. These findings, together with previous reports, suggest that early in the Sarcopterygii lineage, GHRHR and PRPR have already established diverged and specific affinities towards their cognate ligands. GHRHR(2), which has only been found in xenopus, zebrafish and chicken hitherto, accommodates both GHRH and PRP.